Detecting variation in starch granule size and morphology by high-throughput microscopy and flow cytometry. (1st January 2023) - Thieme, Mercedes; Hochmuth, Anton; Ilse, Theresa Elisabeth; Cuesta-Seijo, Jose A.; Stoma, Szymon; Meier, Roger; Nørrelykke, Simon Flyvbjerg; Pedas, Pai Rosager; Braumann, Ilka; Zeeman, Samuel C.
Abstract: Starch forms semi-crystalline, water-insoluble granules, the size and morphology of which vary according to biological origin. These traits, together with polymer composition and structure, determine the physicochemical properties of starch. However, screening methods to identify differences in starch granule size and shape are lacking. Here, we present two approaches for high-throughput starch granule extraction and size determination using flow cytometry and automated, high-throughput light microscopy. We evaluated the practicality of both methods using starch from different species and tissues and demonstrated their effectiveness by screening for induced variation in starch extracted from over 10, 000 barley lines, yielding four with heritable changes in the ratio of large A-granules to small B-granules. Analysis of Arabidopsis lines altered in starch biosynthesis further demonstrates the applicability of these approaches. Identifying variation in starch granule size and shape will enable identification of trait-controlling genes for developing crops with desired properties, and could help optimise starch processing. Graphical abstract: Unlabelled Image